Effects of wet CO oxidation on the operation of engines and power generators - Costa, F. de S. (2003)
A simplified method is used to determine the optimum water content in the flue gases of charcoal gasifiers to be utilized as alternative fuels in the operation of engines and gas turbines for power generation. Computational models of plug flow reactors and well stirred reactors are employed to simulate the reaction and post-flame zones, adopting different chemical mechanisms. In the simulations reactants enter the reactors at 1000 K, 1 atm and equivalence ratio 0.25. It was observed that mixtures about 3% to 4% in volume of water vapor allow to obtain optimal operation characteristics, including high blowout limit, low ignition delay, maximum reaction zone temperature, high CO2 prodution and low thermal NO formation. It was observed that increasing water contents reduce significantly ignition times up to 3% in volume, while blowout mass flow rates increase continuously up to 6 % in volume, the maximum value considered. Formation of NO decreases continuously with humidity after the flame zone, while there are peaks of NO formation within the flame zone below 1% in volume. Higher water vapor content decreases the final temperatures below 1700 K, leading to a lower thermal efficiency. The method can be used to estimate optimum operational conditions with other input parameters.